BRIDGING THEORY AND PRACTICE IN ISLAMIC ECONOMICS: A PRISMA-BASED SYSTEMATIC REVIEW ON ZAKAT, WAQF, AND ISLAMIC SOCIAL FINANCE FOR WELFARE ENHANCEMENT - Marlina Ekawaty; Mochammad Rizki Hanafiansyah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Islamic economics operates as a normative framework prioritizing social justice, equitable wealth redistribution, and collective wellbeing. Despite its robust philosophical foundations, empirical consensus regarding how these tenets translate into measurable welfare outcomes across heterogeneous developing nations remains highly fragmented. This study addresses this critical gap by executing a systematic literature review guided by the PRISMA 2020 statement to synthesize empirical evidence on the operationalization of Zakat, Waqf, and Islamic Social Finance (ISF) as structural instruments for poverty reduction. Departing from traditional descriptive reviews, this paper introduces an original analytical taxonomy that maps the operational mechanics of ISF against micro-level and macro-level development outcomes. Based on a rigorous multi-stage screening of peer-reviewed empirical studies published between 2020 and 2025 across emerging economies, a final synthesized sample of $n = 10$ high-quality primary articles was evaluated. The qualitative narrative synthesis reveals that integrated ISF instruments exert a structurally positive impact on poverty alleviation, income optimization, and socio-economic empowerment, particularly when embedded within digital financial ecosystems and formal financial inclusion frameworks. However, the analysis uncovers substantial outcome heterogeneity, demonstrating that welfare efficacy is highly conditional upon institutional governance quality, targeting accuracy, and localized implementation designs. The structural novelty of this research lies in its empirical crystallization of the explicit boundary conditions under which normative faith-based capital successfully disrupts poverty traps, offering an evidence-based operational blueprint for policymakers and Sharia social institutions in the Global South.